The Prevalence of Autoimmune Thyroiditis in A sample of Infertile Iraqi Women - Frayyeh, Maha J.; Fakhridin, Muhammad- Baqir M. R.; Al-Lami, Makarim Q. D. (Iraqi Journal of Science, 2023)
In the present study, the aim was made to identify the relationship between thyroid autoimmunity (TAI) and female infertility. The study was performed on 30 infertile women and 22 age-matched healthy fertile control age (33 ± 5 years). Overall, serum prolactin (PRL), thyroid stimulating hormone (TSH) assay is the key test for the diagnosis and management of hypo and hyperthyroidism. Anti-TPO Ab and anti-TG Ab were measured. The mean ± SE of serum PRL (31.080 ± 3.06) ng/ml was significantly (P<0.05) higher in infertile group compared with control (16.191±1.36) ng/ml. Serum TSH was significantly (P<0.05) higher in infertile group (5.689 ± 1.12) μIU/ml compared to control group (2.282 ± 0.18) μIU/ml. The prevalence of positive thyroid peroxidase antibody (TPO-Ab) was higher infertile women (248.439 ± 88.77) IU/ml than that of the control (15.118 ± 2.75) IU/ml. Also there was significant differences (P<0.05) in Anti-TG Ab titration in infertile women (360.139 ± 210.32) IU/ml compared to control (31.636±4.69) IU/ml. However, when thyroid antibodies were positive, hypothyroidism was more frequent in infertile women as compared to the control group. In the other hand, a significant (P<0.01) positive correlation between TSH hormone and Anti TPO Ab r = 0.37, while non-significant correlation was found between Anti- TG Ab and TSH. The present study demonstrated that autoimmune thyroiditis in infertile women is higher than that in healthy fertile controls.